The diverse functions of small heat shock proteins in the proteostasis network - Reinle, Kevin; Mogk, Axel; Bukau, Bernd (Journal of molecular biology, 2022)
The protein quality control (PQC) system maintains protein homeostasis by counteracting the accumulation of misfolded protein conformers. Substrate degradation and refolding activities executed by ATP-dependent proteases and chaperones constitute major strategies of the proteostasis network. Small heat shock proteins represent ATP-independent chaperones that bind to misfolded proteins, preventing their uncontrolled aggregation. sHsps share the conserved α-crystallin domain (ACD) and gain functional specificity through variable and largely disordered N- and C-terminal extensions (NTE, CTE). They form large, polydisperse oligomers through multiple, weak interactions between NTE/CTEs and ACD dimers. Sequence variations of sHsps and the large variability of sHsp oligomers enable sHsps to fulfill diverse tasks in the PQC network. sHsp oligomers represent inactive yet dynamic resting states that are rapidly deoligomerized and activated upon stress conditions, releasing substrate binding sites in NTEs and ACDs Bound substrates are usually isolated in large sHsp/substrate complexes. This sequestration activity of sHsps represents a third strategy of the proteostasis network. Substrate sequestration reduces the burden for other PQC components during immediate and persistent stress conditions. Sequestered substrates can be released and directed towards refolding pathways by ATP-dependent Hsp70/Hsp100 chaperones or sorted for degradation by autophagic pathways. sHsps can also maintain the dynamic state of phase-separated stress granules (SGs), which store mRNA and translation factors, by reducing the accumulation of misfolded proteins inside SGs and preventing unfolding of SG components. This ensures SG disassembly and regain of translational capacity during recovery periods.
Part of special issue: Protein Interactions in Liquid-Liquid Phase Separation
Available online 14 July 2021
Gesehen am 21.06.2022